Youth Attitudes and Participation in Climate Protest: An International Cities Comparison Frontiers in Political Science Special Issue: Youth Activism in Environmental Politics - Prendergast, Kate; Hayward, Bronwyn; Aoyagi, Midori; Burningham, Kate; Hasan, M Mehedi; Jackson, Tim; Jha, Vimlendu; Kuroki, Larissa; Loukianov, Anastasia; Mattar, Helio; Schudel, Ingrid; Venn, Sue; et al. (Frontiers in Political Science, 2021)
This article examines youth participation the school climate strikes of 2018 and 2019 (also known as #Fridays4Future), through an exploratory study conducted in seven diverse cities. Despite the international nature of the climate strikes, we know little about the factors that influenced youth participation in these protests beyond the global North. This matters because youth of the global South are disproportionately impacted by climate change and there is growing concern that the climate movement is dominated by narratives that marginalize the voices and priorities of Indigenous communities and people of color. In this context, the exploratory research reported here aimed to compare the attitudes of climate protesters (n = 314) and their non-protester peers (n = 1,217), in diverse city samples drawn from a wider study of children and youth aged 12–24 years, living in Christchurch (New Zealand); Dhaka (Bangladesh); Lambeth, London (United Kingdom); Makhanda (South Africa); New Delhi (India); São Paulo (Brazil); and Yokohama (Japan). Using cross-sectional data (N = 1,531) and binary logistic regression models, researchers examined three common explanations for youth participation in protest: availability (biographical and structural), political engagement (reported individual and collective efficacy of strikers and non-strikers), and self-reported biospheric values amongst participants. Results indicate that even in diverse city samples, structural availability (civic skills and organizational membership) predicted strike participation across city samples, but not political engagement (self-efficacy and collective efficacy). Youth who reported that ‘living in harmony with nature and animals’ was important for their wellbeing, were also more likely to strike than their peers. Descriptive statistics indicated that the majority (85 percent) of all protestors in this study agreed climate change was a serious issue and a startling 65 percent said that they think about climate change “all the time”. Reported rates of youth climate protest participation varied across city samples as did the extent to which participants reported having friends take part or expecting climate change to have a personal impact. While the study is exploratory, it points to the need for more extensive research to understand the diversity of youth participation in ‘global climate strikes’.